Mindfulness-based therapy modulates default-mode network connectivity in patients with opioid dependence - Fahmy, Reham; Schmitgen, Mike; Kubera, Katharina Maria; Wolf, Nadine D.; Wolf, Robert Christian (European neuropsychopharmacology, 2019)
Recently, mindfulness-based programs have shown promising clinical effects in the treatment of substance-use disorders (SUD). While several studies linked mindfulness to decreased default mode network (DMN) connectivity in meditators, only a few studies investigated its effects in patients with SUD. This study aimed to detect changes in DMN connectivity in opiate dependent patients receiving mindfulness based therapy (MBT) during their first month of treatment. Data from 32 patients that were assigned to MBT or treatment as usual (TAU) groups was investigated using resting-state functional MRI at 1.5 T before and after four weeks of treatment. Independent Component Analysis was used to investigate distinct (anterior vs. posterior) DMN subsystems. Connectivity changes after treatment were related to measures of impulsivity, distress tolerance and mindfulness. Increased mindfulness scores after treatment were found in patients receiving MBT compared to TAU. Within the anterior DMN, decreased right inferior frontal cortical connectivity was detected in patients who received MBT compared to TAU. In addition, within the MBT-group decreased right superior frontal cortex connectivity was detected after treatment. Inferior frontal cortex function was significantly associated with mindfulness measures. The data suggest that MBT can be useful during abstinence from opiates. In opiate-dependent patients distinct functional connectivity changes within the DMN are associated with MBT.